The effect of mindfulness on work engagement mediated by psychological capital and psychological empowerment - Lysander, Mohammad Ahyar Syafwan; Bintang, Anjas Mutiara; Hadi, Syamsul (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
This study aims to examine the effect of mindfulness on work engagement, mediated by psychological capital and psychological empowerment, among Generation Z employees in Yogyakarta. The primary issue addressed is the rising levels of stress and job demands experienced by this demographic, necessitating effective strategies to boost engagement and mental resilience. Methodology: This study obtained data by questionnaires, with data collected from 100 respondents selected through stratified sampling from the Base Jogja Menfess Community. Data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Finding: The study findings indicate that mindfulness has a positive effect on psychological capital and psychological empowerment, but does not directly influence work engagement. Psychological empowerment emerged as a significant mediator, enhancing work engagement, while psychological capital demonstrated limited influence, possibly due to regional cultural and economic factors. Conclusion: The study concludes that while mindfulness effectively strengthens psychological resilience and empowerment, its impact on work engagement is more pronounced when supported by empowering work environments.